2019
DOI: 10.1016/j.pedneo.2019.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal hemodynamic changes during therapeutic hypothermia and after rewarming in neonatal hypoxic-Ischemic encephalopathy

Abstract: Background: Hypoxic-ischemic encephalopathy (HIE) is associated with disturbances in visceral blood flow velocities. Therapeutic Hypothermia (TH) is a standard of care; however, its impact on gastrointestinal blood flow in infants with HIE is unknown. The objective of this study was to assess gastrointestinal (GI) blood flow and left ventricle output (LVO) in infants with hypoxicischemic encephalopathy during whole body TH and after rewarming. Methods: Serial echocardiography and Doppler evaluation of intestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 28 publications
0
11
0
1
Order By: Relevance
“…Is important to note that LVO is lower in patients receiving therapeutic hypothermia (mean ± SD 126 ± 38 mL/kg/min), so one must be cautious interpreting it. Sakhuja et al [ 124 ] found that celiac artery and superior mesenteric artery blood flow velocity and LVO did not vary during hypothermia but rose after rewarming, suggesting a protective effect of therapeutic hypothermia on the gastrointestinal system [ 124 ].…”
Section: Neonatal Hypoxic–ischemic Encephalopathy: Clinical Aspectsmentioning
confidence: 99%
“…Is important to note that LVO is lower in patients receiving therapeutic hypothermia (mean ± SD 126 ± 38 mL/kg/min), so one must be cautious interpreting it. Sakhuja et al [ 124 ] found that celiac artery and superior mesenteric artery blood flow velocity and LVO did not vary during hypothermia but rose after rewarming, suggesting a protective effect of therapeutic hypothermia on the gastrointestinal system [ 124 ].…”
Section: Neonatal Hypoxic–ischemic Encephalopathy: Clinical Aspectsmentioning
confidence: 99%
“…On the other hand, hypothermia therapy can lead to adverse effects such as gastrointestinal motility disorders, hypokalemia, stress hyperglycemia, pneumonia, and hypoalbuminemia [25]. Patients receiving hypothermia therapy have decreased, or absent bowel motility, and a higher incidence of gastric retention [26,27]. The present study showed that feeding intolerance during early enteral nutrition in patients treated with hypothermia therapy was 2.331 times higher than in patients without such therapy.…”
Section: Discussionmentioning
confidence: 74%
“…Celiac and mesenteric artery flow remained low during hypothermia with a significant increase after rewarming (peak systolic velocity celiac 0.63 to 0.77, + 22%; mesenteric 0.43 to 0.55 m/s. +28%), in line with a simultaneous increase in left ventricular output (106 to 149 ml/kg/min, +40%) (Sakhuja et al, 2019). Along the same line, bosentan absorption in critically ill neonates with pulmonary hypertension is delayed and steady state concentrations were only achieved from postnatal day 5 onwards (Steinhorn et al, 2016).…”
Section: Knowledge On the Impact Of Hypothermia On Adme Processes In mentioning
confidence: 67%
“…Males appear to be less resistant than females (Britton and Kline, 1945), and high body temperature also reduces resistance. In neonatal rats for example, it has been clearly shown that lowering the body temperature from 37 to 30°C during asphyxia has a protective effect (Saeed et al, 1993). Altricial species are more resistant to asphyxia than precocial TABLE 3 | Proposed experimental conditions for in vitro evaluation of the immediate versus delayed effects of hypothermia on activity of drug metabolizing enzymes (DME) and drug transporters (DT).…”
Section: In Vivo Studies In Animal Modelsmentioning
confidence: 99%